Tropical and Subtropical Fruit Crops for the Home Landscape: Alternatives to Citrus - Jonathan H. Crane; Carlos F. Balerdi; Michael S. Orfanedes (EDIS)
Revised! HS-812, an 8-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi and Michael S. Orfanedes, discusses the numerous varieties of tropical and subtropical fruits that can be grown in the home landscape as alternatives to citrus. This version reflects the current situation with respect to citrus disease threats and alters the recommendation for two fruit crops that are considered invasive in south Florida. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.